Interconnections determination between coordinating abilities and the parameters of shooting from standing position among biathletes at the stage of sports specialization - Krukovskiy, N. A.; Soshnikov, N. N. (The Russian Journal of Physical Education and Sport, 2019)
Crisis, connected with the training volumes and intensity limit, in the opinion of the scientists from different countries, can be solved by means of coordinating and technical training system development. The degree of marksmanship training manifestation and the tempo of shooting technique mastering are mainly conditioned by the level of coordinating abilities. Coordinating abilities are very important both for qualitative fulfillment of the separate technical elements and for the process of shooting training, organization and handling in general. Materials. We reveal the interconnections between the specific coordinating abilities of biathletes at the stage of sports specialization and their parameters of shooting from standing position. Research methods. Information sources analysis and summarizing, testing, graphical-mathematical method, experiment, methods of mathematical statistics. Results. For the first time we found the interconnections between the specific coordinating abilities of biathletes at the stage of sports specialization and the parameters of their shooting from standing position. Specific coordinating abilities were estimated with the help of the tests, created according to the criteria described in the book by Lyakh V.I. "Coordinating abilities: diagnostics and development". In shooting from standing position 3 parameters were estimated: time of the 1st shot, time of shooting, close grouping of shots. It is revealed that the leading coordinating abilities of biathletes, at the stage of sports specialization, are the abilities to feel the balance, to react quickly, to differentiate the parameters of movement. Other important abilities are the abilities to orient oneself in space and feel the rhythm. Conclusion. Interconnections determination will help to organize coordinating training taking into account weak points of marksmanship training.